Anthropology in contemporary poetry by Australian First Nations writers - Charon, Mylene (HAL CCSD, 2023)
International audience This paper proposes a non-exhaustive reading journey through contemporary Australian Indigenous poetry about anthropology. It takes as its staring point the introductory comment by Linda Tuhiwai Smith, according to whom First Nations rather write poetry about research than conduct it, because of the power relationships that have historically enfolded in research Decolonizing Methodologies). Poems by Anita Heiss (Wiradjuri), Jeanine Leane (Wiradjuri) and Ellen van Neerven (Mununjali and dutch) are commented, with a highlight on their polemical and agonistic dimension against anthropology. An opening towards other forms of writing is also proposed, with texts from critical theory (Aileen Moreton-Robinson, Goenpul); artistic manifesto (Richard Bell, koori); fiction prose (Tara June Winch, Wiradjuri). Cette communication propose un parcours de lecture, non exhaustif, dédié à la poésie contemporaine australienne autochtone au sujet de l’anthropologie. Elle prend pour point de départ la remarque introductive de Linda Tuhiwai Smith, selon laquelle les Premières Nations préfèrent écrire de la poésie à propos de la recherche plutôt de la pratiquer, en raison des rapports de pouvoir qui s’y sont historiquement déployés (Decolonizing Methodologies). Des poèmes de Anita Heiss (Wiradjuri), Jeanine Leane (Wiradjuri) et Ellen van Neerven (Mununjali et hollandais.e) sont présentés, avec une insistance sur leur dimension polémique, agonistique à l’égard de l’anthropologie. Une ouverture vers d’autres formes d’expression est aussi proposée: la théorie critique (Aileen Moreton-Robinson, Goenpul) le manifeste artistique (Richard Bell, koori) le roman (Tara June Winch, Wiradjuri).